I Heard “Hunedresit?”: Uncovering Language Barriers Among Indonesian Diasporas in Glasgow - Firdausiyah, Hurrotul; Rifai, Ahmad Abu (OKARA: Jurnal Bahasa dan Sastra, 2025)
Despite the history of the 30th of September Movement (Gerakan Tiga Puluh September, G30S) incident and the Indonesian diasporas' status as exiles with feelings of being haunted and separated from their homeland, many Indonesians currently reside abroad. This current study aims to uncover and scrutinize language barriers among Indonesian diasporas in Glasgow, focusing on language barriers encountered, the effects of the language barriers, and adaptation strategies to face the language barriers. The findings of this study uncover that the Indonesian diasporas in Glasgow encompass the language barriers in Glaswegian accents, vocabularies or slang, and the fast pace of Glaswegian speech. The language barrier has significantly affected their living in Glasgow, especially regarding their communication with the locals and their emotional responses. In navigating the language barriers and adjusting to their new environment, the Indonesian diasporas employ various strategies, such as engaging with locals and learning through entertainment. In shedding light on the language barriers experienced by the Indonesian diasporas in Glasgow, this study highlights the imperative to learn and understand the cultures of host countries aimed at mitigating the challenges and obstacles while living over there.